BIOSKIN: A Protocol for the Copenhagen Translational Skin Immunology Biobank and Research Programme - Lone Skov; Jeanne Duus Johansen; Marianne Bengtson Løvendorf (BMJ Open)
Introduction Psoriasis, atopic dermatitis and contact dermatitis are common chronic inflammatory skin diseases that have a significant impact on individuals and society.Methods and analysis The Copenhagen Translational Skin Immunology Biobank and Research Programme (BIOSKIN) is a translational biobank and research study that aims to prospectively collect high-quality biological samples and clinical data from 3000 patients with psoriasis, atopic dermatitis and contact dermatitis over a minimum period of 5 years. The longitudinal open design allows participants to enter and leave the study at different time points depending on their disease and treatment course. At every visit, the investigator collects biological samples, conducts interviews and assembles self-reported questionnaires on disease-specific and general health-related information. Clinical examination and biological sampling will be conducted at enrolment, during and after disease flare, before and after initiation of new treatment and at least once per year. The clinical examination includes dermatological verification of diagnosis, evaluation of disease severity and detailed information on phenotype. The biological samples include blood and when accessible and relevant, skin biopsies, tape strips and skin swabs. The data collected will undergo rigorous statistical analysis using appropriate analytical methods. As of December 2023, 825 patients have been enrolled in the study.Ethics and dissemination The study is approved by the Scientific Ethical Committee of the Capital Region (H-21032986) and the Danish Data Protection Agency. Results will be published in peer-reviewed scientific journals and presented at national and international conferences.